Yeast contribution to melatonin, melatonin isomers and tryptophan ethyl ester during alcoholic fermentation of grape musts. Issue 4 (20th March 2015) - Vigentini, Ileana; Gardana, Claudio; Fracassetti, Daniela; Gabrielli, Mario; Foschino, Roberto; Simonetti, Paolo; Tirelli, Antonio; Iriti, Marcello
Abstract Melatonin (MEL) has been found in some medicinal and food plants, including grapevine, a commodity of particular interest for the production of wine, a beverage of economic relevance. It has also been suggested that MEL in wine may, at least in part, contribute to the health‐promoting properties attributed to this beverage and, possibly, to other traditional Mediterranean foodstuffs. After a preliminary screening of 9 yeast strains in laboratory medium, three selected strains (Saccharomyces cerevisiae EC1118, Torulaspora delbrueckii CBS1146T and Zygosaccharomyces bailii ATCC36947T) were inoculated in experimental musts obtained from 2 white (Moscato and Chardonnay) and 2 red (Croatina and Merlot) grape varieties. The production of MEL, melatonin isomers (MIs) and tryptophan ethyl ester (TEE) was monitored during the alcoholic fermentation. The screening showed that the three investigated strains produced the highest concentrations of MEL and two MIs in optimal growth conditions. However, MEL and MIs were not produced in oenological conditions, but the three strains synthesized high concentrations of a new MI and TEE in musts.